Pengaruh Brand Image, Harga, dan Kualitas Produk terhadap Keputusan Pembelian di Excelso Pakuwon Surabaya - Mey Rio Dwi Bisma; Anita Asnawi; Isro’ani Widayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This quantitative descriptive method research was conducted to see the influence of brand image, price, and product quality on customer purchasing decisions at Excelso Pakuwon Surabaya. Questionnaires were distributed to 100 respondents to collect primary data on their responses. The results of partial hypothesis testing show that brand image and product quality have a significant and positive effect on purchasing decision variables. On the other hand, the price factor was found not to have a significant effect. The results revealed that brand image plays an important role in shaping customers' positive perceptions of Excelso, which is considered to have consistent quality, a cozy atmosphere, and uniqueness that suits customers' lifestyles. Product quality is also an important factor, where customers value the quality of coffee and the variety of menus available. In contrast, price did not have a significant effect, as some respondents felt Excelso's prices were less competitive than its competitors. These findings suggest that Excelso needs to focus on strengthening brand image and product quality to improve purchasing decisions. In addition, a review of the pricing strategy is recommended to better match customer expectations to strengthen market competitiveness.